Environmentally sound technologies for women in agriculture. (International Federation for Women in Agriculture, 1996)
A simple and science-based material that aims to help reduce drudgery and increase efficiency of extension workers while maintaining a clean and healthy environment. It contains topics on animal husbandry and dairying, vegetables and post harvest technologies, organic farming, and other fields of agriculture.